Cover Image, Volume 76, Number 9, September 2020. Issue 9 (13th August 2020) - Maltz, Brenda; Hoyt, Tim; Uomoto, Jay; Herodes, Megan
Abstract : The cover image is based on the Original Article A Case Analysis of Service Member Trauma Processing Related to Art Therapy within a Military Intensive Outpatient Program by Brenda Maltz et al., https://doi.org/10.1002/jclp.22929 .